2015
DOI: 10.1038/onc.2015.294
|View full text |Cite
|
Sign up to set email alerts
|

GNASR201H and KrasG12D cooperate to promote murine pancreatic tumorigenesis recapitulating human intraductal papillary mucinous neoplasm

Abstract: Intraductal papillary mucinous neoplasm (IPMN), the most common pancreatic cystic neoplasm, is known to progress to invasive ductal adenocarcinoma. IPMNs commonly harbor activating somatic mutations in GNAS and KRAS, primarily GNAS(R201H) and KRAS(G12D). GNAS encodes the stimulatory G-protein α subunit (Gsα) that mediates a stimulatory signal to adenylyl cyclase to produce cyclic adenosine monophosphate (cAMP), subsequently activating cAMP-dependent protein kinase A. The GNAS(R201H) mutation results in constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 21 publications
2
67
2
Order By: Relevance
“…The notion of distinct lesions driving the development of IPMN and MCN is reinforced by recent sequencing studies that have identified IPMN/ MCN-specific mutations in GNAS and RNF43 (Wu et al 2011a,b;Dal Molin et al 2013). While one recent study in an inducible GEMM has shown that Gnas mutation cooperates with oncogenic Kras to promote the formation of IPMN (Taki et al 2015), how these signature mutations function to drive the cystic phenotype during exocrine neoplasia remains an understudied area.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac) Pathogenesismentioning
confidence: 98%
“…The notion of distinct lesions driving the development of IPMN and MCN is reinforced by recent sequencing studies that have identified IPMN/ MCN-specific mutations in GNAS and RNF43 (Wu et al 2011a,b;Dal Molin et al 2013). While one recent study in an inducible GEMM has shown that Gnas mutation cooperates with oncogenic Kras to promote the formation of IPMN (Taki et al 2015), how these signature mutations function to drive the cystic phenotype during exocrine neoplasia remains an understudied area.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac) Pathogenesismentioning
confidence: 98%
“…IPMN formation has been observed in several transgenic mouse models, including those with concomitant activation of TGF-alpha, stimulation of Gs-alpha subunit GNAS, deletion of Brg1 , or attenuated Smad4 expression in the context of oncogenic Kras (Bardeesy et al, 2006; Siveke et al, 2007; Taki et al, 2015; von Figura et al, 2014a). Of particular interest is the observation that despite distinct morphological and gene expression signatures of IPMN and PanIN lesions, the resulting tumors are both classified as PDA.…”
Section: Intraductal Papillary Mucinous Neoplasm (Ipmn) Derived Pdamentioning
confidence: 99%
“…In general, GNAS mutations are often in more advanced lesions. A recent experimental study demonstrated that activating mutations in GNAS and KRAS cooperatively promote pancreatic tumorigenesis, which recapitulates IPMN (37).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%